Docetaxel, cisplatin and fluorouracil (DCF) regimen compared with non-taxane-containing palliative chemotherapy for gastric carcinoma: a systematic review and meta-analysis. - Xiao-Long Chen; Xin-Zu Chen; Chen Yang; Yan-Biao Liao; He Li; Li Wang; Kun Yang; Ka Li; Jian-Kun Hu; Bo Zhang; Zhi-Xin Chen; Jia-Ping Chen; et al. (PLoS ONE, 2013)
Background Gastric carcinoma (GC) is one of the highest cancer-mortality diseases with a high incidence rate in Asia. For surgically unfit but medically fit patients, palliative chemotherapy is the main treatment. The chemotherapy regimen of docetaxel, cisplatin and 5-fluorouracil (DCF) has been used to treat the advanced stage or metastatic GC. It is necessary to compare effectiveness and toxicities of DCF regimen with non-taxane-containing palliative chemotherapy for GC. Methods PubMed, EmBase, Cochrane Central Register of Controlled Trials and China National Knowledge Infrastructure databases were searched to select relative randomized controlled trials (RCTs) comparing DCF to non-taxane-containing chemotherapy for patients with palliatively resected, unresectable, recurrent or metastatic GC. Primary outcome measures were 1-year and 2-year overall survival (OS) rates. Secondary outcome measures were median survival time (MST), median time to progression (TTP), response rate and toxicities. Results Twelve RCTs were eligible and 1089 patients were analyzed totally (549 in DCF and 540 in control). DCF regimen increased partial response rate (38.8% vs 27.9%, p = 0.0003) and reduced progressive disease rate (18.9% vs 33.3%, p = 0.0005) compared to control regimen. Significant improvement of 2-year OS rate was found in DCF regimen (RR = 2.03, p = 0.006), but not of 1-year OS rate (RR = 1.22, p = 0.08). MST was significantly prolonged by DCF regimen (p = 0.039), but not median TTP (p = 0.054). Both 1-year OS rate and median TTP had a trend of prolongation by DCF regimen. Chemotherapy-related mortality was comparable (RR = 1.23, p = 0.49) in both regimens. In grade I-IV toxicities, DCF regimen showed a major raise of febrile neutropenia (RR = 2.33, p<0.0001) and minor raises of leucopenia (RR = 1.25, p<0.00001), neutropenia (RR = 1.19, p<0.00001), and diarrhea (RR = 1.59, p<0.00001), while in other toxicities there were no significant differences. Conclusion DCF regimen has better response than non-taxane containing regimen and could potentially improve the survival outcomes. The chemotherapy-related toxicity of DCF regimen is acceptable to some extent.